High latex yielding and disease resistance of rubber clones IRR 200 series (KUMPULAN JURNAL DOSEN UNIVERSITAS MUHAMMADIYAH SUMATERA UTARA, 2012)
Rubber clones of Indonesian Rubber Research (IRR) 200 series have been produced from intensive breeding program started in 1985. Some clones showed superior characteristics such as high latex yielding, vigorous, and disease resistant. This study aimed test their performances in a field trial conducted since 1999 at Sungei Putih Experimental Garden, North Sumatra. The experiment was designed in a randomized block, using twelve IRR clones as treatment and PB 260 clone as control, three replications. Planting distance was 5 m x 4 m and plot size was rows x 50 trees. Observations were made on girth size of the lateks